A Comprehensive Evaluation of the Relationship Between Different IgG and IgA Anti-Modified Protein Autoantibodies in Rheumatoid Arthritis - Grönwall, Caroline; Liljefors, Lisa; Bang, Holger; Hensvold, Aase H.; Hansson, Monika; Mathsson-Alm, Linda; Israelsson, Lena; Joshua, Vijay; Svärd, Anna; Stålesen, Ragnhild; Titcombe, Philip J.; Steen, Johanna; et al. (Frontiers in Immunology, 2021)
Seropositive rheumatoid arthritis (RA) is characterized by the presence of rheumatoid factor (RF) and anti-citrullinated protein autoantibodies (ACPA) with different fine-specificities. Yet, other serum anti-modified protein autoantibodies (AMPA), e.g. anti-carbamylated (Carb), -acetylated (KAc), and malondialdehyde acetaldehyde (MAA) modified protein antibodies, have been described. In this comprehensive study, we analyze 30 different IgG and IgA AMPA reactivities to Cit, Carb, KAc, and MAA antigens detected by ELISA and autoantigen arrays in N=1985 newly diagnosed RA patients. Association with patient characteristics such as smoking and disease activity were explored. Carb and KAc reactivities by different assays were primarily seen in patients also positive for anti-citrulline reactivity. Modified vimentin (mod-Vim) peptides were used for direct comparison of different AMPA reactivities, revealing that IgA AMPA recognizing mod-Vim was mainly detected in subsets of patients with high IgG anti-Cit-Vim levels and a history of smoking. IgG reactivity to acetylation was mainly detected in a subset of patients with Cit and Carb reactivity. Anti-acetylated histone reactivity was RA-specific and associated with high anti-CCP2 IgG levels, multiple ACPA fine-specificities, and smoking status. This reactivity was also found to be present in CCP2+ RA-risk individuals without arthritis. Our data further demonstrate that IgG autoreactivity to MAA was increased in RA compared to controls with highest levels in CCP2+ RA, but was not RA-specific, and showed low correlation with other AMPA. Anti-MAA was instead associated with disease activity and was not significantly increased in CCP2+ individuals at risk of RA. Notably, RA patients could be subdivided into four different subsets based on their AMPA IgG and IgA reactivity profiles. Our serology results were complemented by screening of monoclonal antibodies derived from single B cells from RA patients for the same antigens as the RA cohort. Certain CCP2+ clones had Carb or Carb+KAc+ multireactivity, while such reactivities were not found in CCP2- clones. We conclude that autoantibodies exhibiting different patterns of ACPA fine-specificities as well as Carb and KAc reactivity are present in RA and may be derived from multireactive B-cell clones. Carb and KAc could be considered reactivities within the “Cit-umbrella” similar to ACPA fine-specificities, while MAA reactivity is distinctly different.